Assessment of the Cow's Milk-related Symptom Score (CoMiSS) as a diagnostic tool for cow's milk protein allergy: a prospective, multicentre study in China (MOSAIC study). Issue 2 (17th February 2022) - Vandenplas, Yvan; Zhao, Zheng-Yan; Mukherjee, Rajat; Dupont, Christophe; Eigenmann, Philippe; Kuitunen, Mikael; Ribes Koninckx, Carmen; Szajewska, Hania; von Berg, Andrea; Bajerová, Kateřina; Meyer, Rosan; Salvatore, Silvia; et al.
Abstract : Objectives: The MOSAIC study aimed to evaluate if the Cow's Milk-related Symptom Score (CoMiSS) can be used as a stand-alone diagnostic tool for cow's milk protein allergy (CMPA). Design: Single-blinded, prospective, multicentre diagnostic accuracy study. Setting: 10 paediatric centres in China. Participants: 300 non-breastfed infants (median age 16.1 weeks) with suspected CMPA. Interventions: After performing the baseline CoMiSS, infants commenced a cow's milk protein elimination diet with amino acid-based formula for 14 days. CoMiSS was repeated at the end of the elimination trial. Infants then underwent an open oral food challenge (OFC) with cow's milk-based formula (CMF) in hospital. Infants who did not react during the OFC also completed a 14-day home challenge with CMF. A diagnosis of CMPA was made if acute or delayed reactions were reported. Primary outcome measures: A logistic regression model for CoMiSS to predict CMPA was fitted and a receiver–operator characteristic (ROC) curve generated. An area under the curve (AUC) of ≥0.75 was deemed adequate to validate CoMiSS as a diagnostic tool (target sensitivity 80%–90% and specificity 60%–70%). Results: Of 254 infants who commenced the OFC, 250 completed both challenges, and a diagnosis of CMPA made in 217 (85.4%). The median baseline CoMiSS in this group fell from 8 (IQR 5–10) to 5 (IQR 3–7) at visit 2 (p<0.000000001), with a median change of −3 (IQR −6 to −1). A baseline CoMiSS of ≥12 had a low sensitivity (20.3%), but high specificity (87.9%) and high positive predictive value (91.7%) for CMPA. The ROC analysis with an AUC of 0.67 fell short of the predefined primary endpoint. Conclusions: The present study did not support the use of CoMiSS as a stand-alone diagnostic tool for CMPA. Nevertheless, CoMiSS remains a clinically useful awareness tool to help identify infants with cow's milk-related symptoms. Trial registration number: NCT03004729 ; Pre-results.